Game analysis of Olympic, World and European Championships in men`s handball - Bilge, M. (Journal of Human Kinetics, 2012)
The development of men`s handball was analyzed using data from the Olympic, World and European Championships held within the last eight years. The most obvious change, especially within these last nine tournaments, was that men`s handball was played more dynamically and rapidly, both in attack and defense, especially by European teams. The first aim of this study was to conduct a technical analysis of current handball and to determine factors related to success in this sport discipline. The second aim was to compare the data of European Championships with other tournaments, considering the success of European teams in Men`s World Handball. The technical variables used to compare the tournaments included: the average number of attacks, the efficiency of attacks, the efficiency of goal throws, fast break goals per game, the efficiency of fast breaks, the efficiency of the goalkeeper, saves by the goalkeeper per game, number of turnovers per game, and the efficiency of position throws (wing, pivot, back court, break-through, fast break, and 7-meter). This technical analysis used cumulative statistics from the European Handball Federation and International Handball Federation. ANOVA revealed significant differences between the first eight teams in the European Championships and their counterparts in the other two tournaments (Olympics and World Championships) in terms of several technical variables. The results showed that the efficiency of fast break, pivot position and back court players affected the ranking in favor of the European teams in significant international tournaments.